(519/Pdt.P/2018/PA.Sby):Ù†Ø¸Ø± Ø§Ù„Ù‚Ø¶Ø§Ø© ÙÙŠ Ø±Ø®ØµØ© Ø§Ù„Ù†ÙƒØ§Ø Ø§Ù„Ù…Ø¨ÙƒØ± (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¹Ù† Ù‚Ø±Ø§Ø± Ø§Ù„Ù…ØÙƒÙ…Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø³ÙˆØ±Ø§Ø¨Ø§ÙŠØ§ Ø±Ù‚Ù… - Wahyudi, Agus; Mulyono, Mulyono; Masduqi, Ahmad (Maqasid: Jurnal Studi Hukum Islam, 2020)
ABSTRACT In Indonesia, age is one of the requirements for someone who wants to get married. The existence of the law on marriage age restrictions is for the benefit of family and marriage as regulated in article 7 paragraph 1 of Law No.1 of 1974 that in marriage the bride must be 19 years old and the bride must be 16 years old If this is not fulfilled, the marriage dispensation provided by the Religious Courts must be used. In the Decision of the Surabaya Religious Court number (519/ Pdt.P/2018/PA.Sby) the judge granted the petition of the petitioner, namely giving a dispensation to the applicant's child who had not yet been sentenced to age for marriage. As for this study to determine the judge's consideration of early marriage dispensation based on the Decision of the Surabaya Religious Court number (519/Pdt.P/2018/PA.Sby) and to find out the decision in the perspective of Islamic law. The method used by the authors in this study is a qualitative or empirical method with documentation data collection techniques which are then analyzed to obta in conclusions From the results of the research conducted it can be concluded that, the judge's consideration in deciding the case (519/Pdt.P/2018/PA.Sby) first though the applicant's child had not reached the age of 19 years as stipulated in law number 1 of 1974 but the applicant's child showed his ability to get married then in order to prevent the judge from being obedient, he granted the petitioner's request by providing a marriage dispensation. Both court rulings are in accordance with Islamic law because the Shari'a do not provide a certain age limit for marriage.Keywords: Judge Considerations, Marriage, Early Marriage Dispensation